The severity and spread of adjustment problems of adolescents involved in mutually hostile interactions with others. (19th December 2017) - Stattin, Håkan; Latina, Delia
ABSTRACT: In the literature, bully‐victims report a wider range of adjustment problems than "pure" bullies or victims. This may not be confined to the school context, but might be found in other settings as well. Involvement in mutually hostile interactions across everyday settings may more reflect adolescents' characteristic way of handling conflicts with others. We used data from a longitudinal study of a community sample of adolescents (N = 992). Cluster analyses for specific everyday settings and across settings yielded clusters high on both exposing others and being exposed to hostility. Adolescents in these clusters, and particularly across settings, reported a wider range of externalizing, internalizing, and academic problems, than adolescents in other cluster groups. Longitudinal analyses showed support for bidirectional relationships between mutually hostile conditions and problematic adjustment. We conclude that adolescents' mutual hostility experiences are associated with profoundly problematic adjustment.